2020
DOI: 10.3389/fpsyg.2020.01954
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory as an Indicator for Comparative Cognition – Detecting Qualitative and Quantitative Differences

Abstract: Working memory (WM), the representation of information held accessible for manipulation over time, is an essential component of all higher cognitive abilities. It allows for complex behaviors that go beyond simple stimulus-response associations and inflexible behavioral patterns. WM capacity determines how many different pieces of information (items) can be used for these cognitive processes, and in humans, it correlates with fluid intelligence. As such, WM might be a useful tool for comparison of cognition ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 105 publications
(167 reference statements)
0
11
0
Order By: Relevance
“…Thus, these data indicate that this group of volunteers show an improvement in the quality of working memory [ 51 ], which in turn reflects an improvement in cognitive abilities [ 52 ]. Furthermore, our data also reveal an accuracy response elevation and response time reduction in the digit vigilance task, a validity test for assessing attention [ 53 , 54 , 55 , 56 ]. Therefore, these data point out that the supplement containing the functional ingredient at a dose of 1500 mg per day can enhance attention and working memory, which in turn indirectly indicates an improvement in cognitive processing abilities.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, these data indicate that this group of volunteers show an improvement in the quality of working memory [ 51 ], which in turn reflects an improvement in cognitive abilities [ 52 ]. Furthermore, our data also reveal an accuracy response elevation and response time reduction in the digit vigilance task, a validity test for assessing attention [ 53 , 54 , 55 , 56 ]. Therefore, these data point out that the supplement containing the functional ingredient at a dose of 1500 mg per day can enhance attention and working memory, which in turn indirectly indicates an improvement in cognitive processing abilities.…”
Section: Discussionmentioning
confidence: 68%
“…The ability to discriminate between and within experienced states is critical for control over behavior, an important part of one’s cognitive skills closely related to working memory [ 51 , 52 , 53 , 54 ]. In addition to arguing about the nature and definition of this concept, it has been demonstrated that various neural areas are involved in its functioning [ 55 , 56 , 57 , 58 ].…”
Section: Methods Of Studying Consciousness In Contemporary Sciencementioning
confidence: 99%
“…It permits flexibility of responding by allowing details of the situation to be incorporated into the choice of response. Ultimately, all mental processes from remembering something no longer sensed, or knowing the way home; to problem-solving, thinking, and planning; requires that relevant information be held in STM and activated by attention for processing ( Roth, 2013 ; Hahn and Rose, 2020 ; Buschman, 2021 ). The WM mechanism is a basic component of mind 1 that is necessary for all response systems (other than S-R mechanisms) to function.…”
Section: The Evolution Of Wm and Its Possible Loss In Some Speciesmentioning
confidence: 99%